Epigenetic associations with adolescent grey matter maturation and cognitive development - Jensen, Dawn; Chen, Jiayu; Turner, Jessica A.; Stephen, Julia M.; Wang, Yu-Ping; Wilson, Tony W.; Calhoun, Vince D.; Liu, Jingyu (Frontiers in Genetics, 2023)
Adolescence, a critical phase of human neurodevelopment, is marked by a tremendous reorganization of the brain and accompanied by improved cognitive performance. This development is driven in part by gene expression, which in turn is partly regulated by DNA methylation (DNAm). We collected brain imaging, cognitive assessments, and DNAm in a longitudinal cohort of approximately 200 typically developing participants, aged nine to fourteen. This data, from three time points roughly one year apart, was used to explore the relationships between seven cytosine-phosphate-guanine (CpG) sites in genes highly expressed in brain tissues (GRIN2D, GABRB3, KCNC1, SLC12A9, CHD5, STXBP5, and NFASC), seven networks of gray matter (GM) volume change, and scores from seven cognitive tests. The demethylation of the CpGs as well as the rates of change in DNAm were significantly related to improvements in total, crystalized, and fluid cognition scores, executive function, episodic memory, and processing speed, as well as several networks of GM volume increases and decreases that highlight typical patterns of brain maturation. Our study provides a first look at the DNAm of genes involved in myelination, excitatory and inhibitory receptors, and connectivity, how they are related to the large-scale changes occurring in the brain structure as well as cognition during adolescence.